Implementing the National Strategic Plan on Gender-Based Violence and Femicide in South Africa: The challenges of policy implementation - Roberts, Ashleigh-Nicole (Department of Political Studies, 2025)
This paper examines the challenges toward implementing gender-based violence (GBV) interventions under the National Strategic Plan of Gender-Based Violence and Femicide (NSP GBVF) in South Africa. The NSP was introduced in 2020 as a multistakeholder policy to address the high levels of GBV in the country, however, has failed to reach a number of its targets in the first three years. Six semi-structured interviews were conducted with experts in the field, who have worked for organisations that run gender-based violence interventions, to gain insight into their views about the implementation of the NSP as well as GBV prevention efforts in the country. The NSP GBVF was a result of women's and feminist groups organising to bring attention to the government's complicity in the high levels of GBV. South Africa has a strong history of women's movements mobilising behind causes that impact them. Civil society organisations that focus on GBV have been in contention with the government at times, due to the lack of transparency and accountability within the government as well as the perceived lack of political urgency around issues of GBV. The relationship between the government and Civil society organisations is an important one as these organisations bring expert knowledge about the communities they work in, have the potential to increase implementation capacity and hold the government accountable when promises are not met. Currently, the gap between policy and implementation limits the effectiveness of the NSP at a grassroots level. Government needs to be held to greater accountability to ensure the adoption of the national framework at both institutional and grassroots levels. Community engagement is vital as a cultural shift in attitudes around gender and violence is required. South Africa has created gender-responsive policies since 1994, however these policies are not being effectively resourced or implemented which is why there has not been a reduction in GBV rates. The underlying structural causes of GBV need to be addressed in order to achieve results.